2009
DOI: 10.1115/1.4001123
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Properties and Their Effects on Convective Heat Transfer in an Electronics Cooling Application

Abstract: In the search for new, more effective coolant fluids, nanoparticle suspensions have shown promise due to their enhanced thermal conductivity. However, there is a concomitant increase in the viscosity, requiring an increase in pumping power to achieve the same flow rate. Studies of flow cooling in simple geometries indicate that there is a benefit to using nanofluids, but it is difficult to justify extending these results to the far more complicated geometries. Moreover, with the variability of property measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Zeta potential is an electrophoretic property of heterogeneous fluids and is defined as the potential difference between the dispersed particles surface and the layered fluid attached to the particles. If the zeta potential value is below −30 mV or above +30 mV, the suspensions are considered more stable due to strong repulsive force between the charged nanoparticles [10][11][12][13]. This can be obtained with high surface charge density of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Zeta potential is an electrophoretic property of heterogeneous fluids and is defined as the potential difference between the dispersed particles surface and the layered fluid attached to the particles. If the zeta potential value is below −30 mV or above +30 mV, the suspensions are considered more stable due to strong repulsive force between the charged nanoparticles [10][11][12][13]. This can be obtained with high surface charge density of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…), applications have significantly diversified in the past decade. New areas in which nanofluids have been deployed include bioconvection in microbial fuel cells , electronics cooling (Townsend and Christianson 2009), building physics and contamination control (Kulkarni et al 2009), pharmacological administration mechanisms (Mody et al 2013), peristaltic pumps for diabetic treatments and solar collectors (Rana et al 2013a). Experimental works have been complemented in recent years by numerous theoretical and computational simulations.…”
mentioning
confidence: 99%
“…In short, there is some difference between this model and the Maxwell model, albeit small. In Table 2, thermal conductivity values of select concentrations of alumina-water nanofluids calculated using the Maxwell model are reported and compared to published experimental Table 1 The density of alumina-water nanofluids (measured and calculated) measurements reported by Williams et al [17] and Townsend and Christianson [18]. The difference between the experimental measurements and Maxwell theory is also listed in Table 2 and considered acceptable agreement; note also that the INPBE study showed that the more detailed model proposed by Nan et al [14] only agreed with the measured thermal conductivity to an accuracy of 18% [10].…”
Section: Thermal Conductivitymentioning
confidence: 98%
“…b Measured values for the baseline fluid (water) were compared to NIST data for temperatures between 20 and 80 C. c Values from Eq. (3) were compared to published experimental measurements reported by Williams et al[17] and Townsend and Christianson[18]. d Values from Eq.…”
mentioning
confidence: 99%